The effect of hydro alcoholic extract of AchilleaMillefolium capsule on duration and severity of primary dysmenorrhea pain - Farzaneh Ebrahimi Varzaneh; Fatemeh Nahidi; Faraz Mojab; Mohamad Amin Pourhoseingholi; Zahra Panahi (Mashhad University of Medical Sciences, 2017)
Introduction: Dysmenorrhea is one of the most common gynecological problems in women which can be treated with chemical drugs, herbal medicines, acupuncture, acupressure, and massage therapy. With regard to the possible positive effect of Achillea-Millefolium (AM) on dysmenorrhea and lack of adequate studies in the area, this study was performed with aim to investigate the effect of extract capsule of AM on duration and severity of primary dysmenorrheal pain. Methods: This triple-blind randomized controlled clinical trial was performed on 50 women referring to Valiears health center affiliated to Tehran University of Medical Sciences in 2015-2016. The subjects were divided into intervention and control group. During three first day of menstruation, the intervention group was treated with 150mg AM capsule for every eight hours and 250mg Mefenamic-acid capsules for every six hours, and control group was treated with AM placebo capsules and Mefenamic-acid capsules during two consecutive months. The study tools were demographic questionnaire and visual analogue scale (VAS). The severity of pain was measured by visual analogue scale (VAS) and duration of pain was measured by the day (one cycle before the study and two cycle during the intervention). Data was analyzed by SPSS software (version 22) and t-independent statistical tests, Mann-Whitney, Fisher and Friedman tests. PResults: Before the intervention, two groups were similar in terms of pain severity and duration of pain. During two cycles of intervention, pain severity and duration of pain significantly decreased (P<0.05) in both groups. However, decreased pain severity was significantly higher in the intervention group (P<0.001), but decreased duration of pain had no significant difference between two groups (P>0.05). Conclusion: Decreased dysmenorrheal pain was higher in the group of AM and Mefenamic-acid capsules compared to the group of Mefenamic-acid capsules that may be is due to the effect of AM on dysmenorrheal pain.